2005
DOI: 10.1007/s10775-005-8799-9
|View full text |Cite
|
Sign up to set email alerts
|

International Best Practices in Career Development: Review of the Literature

Abstract: This paper presents a review of the literature to identify exemplary international career planning programs. Following the National Career Development Guidelines as a guide, a framework was created to organize the research: Content, process, and infrastructure. This review of the literature supports the general tenets of career development -that self-knowledge and career exploration, and an interactive and integrated method of delivery, are key to sound career decisionmaking. The focus of the international com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 13 publications
0
30
0
1
Order By: Relevance
“…Computer-based career planning systems such as SIGI PLUS and DISCOVER are already commonplace in developed countries (Reile and Harris-Bowlsbey 2000;Richard 2005). However, the vast majority of the respondents (94%) reported not even being aware of computer-based career planning systems.…”
Section: Utilization Of Ict Tools In Guidance Workmentioning
confidence: 99%
“…Computer-based career planning systems such as SIGI PLUS and DISCOVER are already commonplace in developed countries (Reile and Harris-Bowlsbey 2000;Richard 2005). However, the vast majority of the respondents (94%) reported not even being aware of computer-based career planning systems.…”
Section: Utilization Of Ict Tools In Guidance Workmentioning
confidence: 99%
“…Stanbury (2005) characterized benchmarking for career development as reference points that are not fixed, but provide a shared understanding for discussing what is and what could be. Richard's (2005) review of published journal articles that described exemplary career programs resulted in a framework for career program content, process and infrastructure. He concluded that there is great benefit for the improvement of career practice by discerning what has been seen to be effective in a range of contexts.…”
Section: Benchmarkingmentioning
confidence: 99%
“…In an extensive review of the best international career development practices, Richard (2005) says that for these practices to be effective there must be certain components to their content. This content includes increased self-knowledge, gathering of information, and decision-making and planning skills.…”
Section: Current Researchmentioning
confidence: 99%
“…Thus, as Leppel (2005) mentioned, their future utility will outweigh their current utility and will increase the likelihood of their persistence. Each of the essential components for a successful course that impacts retention mentioned by Richard (2005) will be fulfilled as well. Both declared and predeclared students can emerge from this class with a well-outlined plan and a way of achieving it.…”
Section: / Conner Daugherty and Gilmorementioning
confidence: 99%